Ecotheology in Minangkabau Community Education: Integration with the Leadership Management of Niniak Mamak - Eramli Jantan Abdullah; Febrino, Febrino; Rashed , Zetty Nurzuliana (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
This study addresses environmental degradation and declining ecological awareness in modern religious and social life. Within the Minangkabau context, the integration of Islamic values and customary traditions continues to reflect a harmonious relationship between humans, nature, and God. This research analyzes how Islamic ecotheological values are embedded in the leadership of niniak mamak (traditional leaders) and the social practices of the Salingka Nagari community in Tilatang Kamang, Agam Regency, West Sumatra. Using a qualitative descriptive-analytical approach, data were collected through in-depth interviews, participatory observation, and documentation, with Tamsir Dt. Pado Batuah and Mutaqim Malin Pamuncak serving as key informants. The findings show that Islamic ecotheological values are practiced through an indigenous leadership system grounded in mizan (ecological balance), amanah (responsibility for God’s creation), and ukhuwah kauniyyah (universal brotherhood among all beings). Ecological governance is reflected in the management of customary forests (Rimbo Manduang), collective farming (batanam basamo), and community deliberation, all rooted in the principle of adat basandi syarak, syarak basandi Kitabullah (custom founded upon Islamic law, and Islamic law founded upon the Qur’an). Non-formal educational spaces such as surau and lapau also function as channels for transmitting ecotheological values across generations. This study concludes that the leadership of niniak mamak in Tilatang Kamang embodies a living model of Islamic social ecology, integrating Islamic teachings, local wisdom, and ecological consciousness within a sustainable governance system. The findings contribute to developing a faith-based ecological leadership framework within Islamic education and sustainable development discourse.